Microhabitat of Endangered Species, Lonchura oryzivora in Malang City, Indonesia - Aryanti, Nirmala Ayu; Abdillah, Fahmi Maulana; Sari, Andini Maya; Pradipta, Naresvara Nircela; Yuda, Pramana (Media Konservasi, 2024)
Malang City, located in Java, Indonesia, faces significant anthropogenic pressures but remains an important habitat for the endangered Java sparrow (Lonchura oryzivora). Understanding how Java sparrows adapt to environments with high levels of human activity is essential for their conservation. This study focused on identifying the distribution of Java sparrows and investigating their habitat selection within Malang City. The bird positions were recorded within the tree canopy, and the frequency of canopy use by the birds was determined. Living in the middle of the city impacts the metabolism of birds, as indicated by taking samples and measuring the levels of lead found in their droppings and vegetation used. Encounters near the center of human activity show they can utilize buildings and vegetation they utilize. The Java sparrows predominantly utilize plant parts at the tree level, particularly focusing on the middle canopy part of the edge (TTt) and the middle part (TT). Laboratory tests revealed that the plants utilized by the Java sparrow contain high lead levels. Therefore, to conserve the Java sparrow, it is crucial to improve the quality of their habitat to make it more natural and conduct regular health monitoring to ensure their well-being.